2020
DOI: 10.3390/ijms21041382
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody Biomarkers in Rheumatic Diseases

Abstract: Autoantibodies encountered in patients with systemic rheumatic diseases bear clinical significance as a biomarker to help or predict diagnosis, clinical phenotypes, prognosis, and treatment decision-making. Furthermore, evidence has accumulated regarding the active involvement of disease-specific or disease-associated autoantibodies in the pathogenic process beyond simple association with the disease, and such knowledge has become essential for us to better understand the clinical value of autoantibodies as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 176 publications
(239 reference statements)
3
33
1
2
Order By: Relevance
“…Our results showed that RF amplified after CFA injection at 10 and 21 but the level began to decline at 21 days without treatment; these findings were the same as other results [20,21], also an augmentation in MDA at 10 and 21 days of induction; this was in the accordance with Akyol et al, founded a remarkable elevation in MDA levels in patients with RA compared to controls [22], this was also observed by [23]; discussed that increased levels of S-nitrosothiols are present in RA plasma and knee-joint synovial fluid, which correlated with measures of inflammation in RA [24].…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that RF amplified after CFA injection at 10 and 21 but the level began to decline at 21 days without treatment; these findings were the same as other results [20,21], also an augmentation in MDA at 10 and 21 days of induction; this was in the accordance with Akyol et al, founded a remarkable elevation in MDA levels in patients with RA compared to controls [22], this was also observed by [23]; discussed that increased levels of S-nitrosothiols are present in RA plasma and knee-joint synovial fluid, which correlated with measures of inflammation in RA [24].…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, the sole consideration of healthy donors in control groups may lead to overestimated assay specificity, as the impact of potential cross-reactive factors present in the general population is largely ignored. In this respect, auto-antibodies commonly found in individuals with inflammatory diseases (22) were already described to cross-react with SARS-CoV-1 antigens (23). To challenge our tests systems, we biased our large specificity cohort (n=1,126) by including samples with an increased propensity for cross-reactivity, including sera from individuals with inflammatory illnesses (n=359), sera from PCR-confirmed hCoV infections (n=8) and sera drawn during winter months to increase the likelihood of respiratory infections (n=494).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the sole consideration of healthy donors in control groups may lead to overestimated assay specificity, as the impact of potential cross-reactive factors present in the general population is largely ignored. In this respect, auto-antibodies commonly found in individuals with inflammatory diseases [58] were already described to cross-react with SARS-CoV-1 antigens [59] . To challenge our tests systems, we biased our large specificity cohort ( n = 1126) by including samples with an increased propensity for cross-reactivity, including sera from individuals with inflammatory illnesses ( n = 359), sera from PCR-confirmed hCoV infections ( n = 8) and sera drawn during winter months to increase the likelihood of respiratory infections ( n = 494).…”
Section: Discussionmentioning
confidence: 99%